1996
DOI: 10.1111/j.1365-2672.1996.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and level of Listeria monocytogenes contamination of food sources at primary production and initial processing

Abstract: 1996. Listeria monocytogenes was isolated in low numbers from a variety of environmental samples associated with the primary production of food, including vegetation, faeces and meat. T h e organism was rarely detected on growing grass and vegetables prior to processing. The excretion of L. monocytogenes by farm animals was linked to their diet, with animals fed entirely on hay or manufactured diets not excreting detectable levels of Listeria (i.e. absence in 25 g). However, animals fed on silage, which is fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…L. monocytogenes is an intracellular Grampositive non-sporulating pathogenic bacterium with wide spread presence in nature, affecting a wide range of domestic and wild animals and humans [6]. In the vast majority of human cases, infection is the result of consumption of contaminated food [7]. Although the infectious dose remains unknown and is most likely host dependent, the resulting invasive disease, listeriosis, is a serious illness with a high fatality rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes is an intracellular Grampositive non-sporulating pathogenic bacterium with wide spread presence in nature, affecting a wide range of domestic and wild animals and humans [6]. In the vast majority of human cases, infection is the result of consumption of contaminated food [7]. Although the infectious dose remains unknown and is most likely host dependent, the resulting invasive disease, listeriosis, is a serious illness with a high fatality rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, post-processing contamination of product with strains associated with the processing environment can occur (Harvey & Gilmour, 1993). Furthermore, various studies have indicated that certain strains of L. monocytogenes survive within the food processing environment (Fenlon, 1996;Nørrung & Skovgaard, 1993;Senczek, Stephan, & Untermann, 2000;Unnerstad et al, 1996) and the persistence of such strains in a food processing plant is of particular concern as they have the potential to act as a continual source of contamination of the processed product (Sashara & Zottola, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes is a food-borne pathogen widely distributed throughout the natural environment (Fenlon, Wilson, & Donachie, 1996) and consequently, it is present in many animal and plant food products. Its extended distribution throughout the environment and the psychrotrophic character of the pathogen, appear to be the main causes of its high prevalence in different kinds of refrigerated ready-to-eat products (RTE) (Lianou & Sofos, 2007).…”
Section: Introductionmentioning
confidence: 99%